Predicting Elevations.of Water Surface in A Tidal Water System (Malaysian Journal of Civil Engineering, 2018)
In predicting the tidal elevations in the Back Bay of Biloxi in Mississippi, the WaterQuality Analysis Simulation-S (WASP5) hydrodynamics model DYNHYD5 wasutilized. Model calibration of the tidal elevations was initially accomplishedutilizing historical data collected by the U.S. Geological Survey (USGS) during theperiod June 14-16, 1977 along with a second set of data collected by the U. S.Environmental Protection Agency (USEPA) during the period July 28-August 2,1972. Final model calibration was performed utilizing a set of field data acquiredon the Back Bay of Biloxi, during September 12-21, 1994 and during April 25 May2, 1995. Comparisons of the predicted and observed tidal data are madequalitatively by using temporal comparisons. The respon se of model predictioncalculations is consistent with trends of the observed data ranges, but not withabsolute values in all cases. The results indicate that the model can accuratelypredict the tidal elevations in the Bay under varying conditions of estuarine flow .